Effects of Two Different Resistance-Training Programs on Mean Tennis-Serve Velocity in Adolescents - Behringer, M.; Neuerburg, S.; Matthews, M.; Mester, J. (Pediatric Exercise Science, 2013)
The purpose of the current study was to evaluate the transferability of 2 different resistance training protocols on service velocity and its precision consistency in junior tennis players. Thirty-six male athletes (15.03 ± 1.64 years) were randomly assigned to a machine-based resistance-training group (RG, n = 12), a plyometric training group (PG, n = 12), and a control group (CG, n = 12). For a period of 8 weeks, both intervention groups resistance trained 2 days per week in addition to their regular tennis training, whereas the CG had no extra training. Mean service velocity over 20 maximum-velocity serves increased significantly more in PG (3.78%; p < .05) when compared with CG, whereas no such changes could be found in the RG (1.18%; p > .05). Service precision did not change from pre- to posttest in all three groups (p > .05). Only the plyometric training program tested, improved mean service velocity over 20 maximum-velocity serves in junior tennis players but did not affect service precision.